Relationship between ferroptosis and healing of diabetic foot ulcer: a prospective clinical study - Qian Jiang; Long Tang; Shuao Xiao (Frontiers in Endocrinology)
ObjectiveDiabetic foot ulcer (DFU) is one of the common complications in patients with diabetes mellitus (DM). In order to find a method to monitor and treat the refractory DFU, the ferroptosis level in DFU and traumatic wounds (TW) was monitored and the difference between them was analyzed. At the same time, this study further analyzed the correlation of ferroptosis levels with DM severity and DFU’s healing.MethodsA prospective cohort study was from January, 2021 to December, 2023 in the Second People’s Hospital of Gansu province, which included 59 patients with DFU and 42 patients with TW. We then used the kit to detect the indicators related to ferroptosis, including 4-Hydroxynonenal (4-HNE), Malondialdehyde (MDA) and reactive oxygen species (ROS), in the wound exudate of the two groups of patients.ResultsThe DFU group had higher ferroptosis level than the TW group (4-HNE: P = 0.003, MDA: P<0.001, ROS: P<0.001). The severity of diabetes was significantly associated with ferroptosis level in DFU patients(r = 0.936, P <0.001). The results of multiple regression analysis showed that 4-HNE (β = -0.182, P = 0.008), MDA (β = -0.478, P <0.001) and ROS (β = -0.394, P<0.001) significantly negatively predicted the healing rate of DFU.ConclusionAs a new monitoring and therapeutic target, ferroptosis level plays an important role in predicting the healing rate of DFU and assisting clinical treatment decision-making.